Holographically-Guided Endovascular Aneurysm Repair. (August 2019) - Rynio, Paweł; Witowski, Jan; Kamiński, Jakub; Serafin, Jakub; Kazimierczak, Arkadiusz; Gutowski, Piotr
Purpose: To demonstrate the feasibility of augmented reality visualization in planning and navigating endovascular aortic repair.Technique: A 77-year-old patient with abdominal aortic aneurysm was treated with endovascular repair. An augmented reality head-mounted display was used during the procedure. The aneurysm and bones were projected as 3-dimensional holograms. The operator controlled the device with gestures and voice commands (movement, rotation, cutting through, and zooming). Moreover, the hologram was placed in front of the angiography monitor and manually registered with fluoroscopy.Conclusion: Augmented reality with holographic rendering is feasible and helpful during endovascular aortic repair. Its routine use could possibly lead to shorter operating time, reduced contrast volume, and lower radiation dose; however, larger studies are required to obtain statistically significant results on the outcomes.